Real-World Efficacy of Tirbanibulin in Actinic Keratosis Treatment: Expert Consensus and Clinical Insights - Ardigò, Marco; Argenziano, Giuseppe; Campione, Elena; Guida, Stefania; Longo, Caterina; Micali, Giuseppe; Nazzaro, Gianluca; Peris, Ketty; Venturi, Federico; Villani, Alessia; Zalaudek, Iris (Dermatology Practical & Conceptual, 2025)
Introduction: Tirbanibulin, a topical treatment for actinic keratosis (AK) with a novel antiproliferative mechanism of action, has demonstrated efficacy and a favorable tolerability profile in clinical trials and real-life studies. An insight into best-practice use of tirbanibulin in different clinical presentations of AK would be useful. Objectives: The aim of this article is to deliver advice, via expert consensus, on optimal use of tirbanibulin in the real-life management of AK. Methods: A panel of 11 dermatologists with expertise in the treatment of AK convened to develop consensus statements about key aspects of tirbanibulin treatment in AK patients, based on selected literature data and their own clinical experience. Results: Two areas were examined and discussed: clinical assessment/diagnostic procedures and key aspects of tirbanibulin therapy. A total of 19 statements were elaborated and voted, concerning clinical evaluation of AK patients, routine and advanced diagnostic instruments, patient selection, treatment modalities and key messages for patient communication. Conclusion: Tirbanibulin should be considered as a first-line option for most patients with AK, owing to its proven efficacy, good local and systemic tolerability and a short treatment regimen of 5 days. All these factors encourage patient acceptability and treatment compliance. The favorable safety profile and tolerability of tirbanibulin also makes it possible to use flexible therapeutic schedules, including repeated treatment cycles, if needed.